A MOF / cellulose composite nanofluid channel membrane and its preparation method and application

By loading MOF particles on cellulose nano -fiber to form MOF/cellulose composite membrane, the existing nano fluid membrane has the lack of ion transmission and infiltration capacity, and achieves high -efficiency ion transmission and high osmosis energy conversion performance.

CN115182163BInactive Publication Date: 2025-01-28NANJING FORESTRY UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210839994.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-18
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing nanofluid films have problems in complex preparation methods, high raw material costs, low charge density, poor water stability, high ion transmission energy barrier and low current output, making it difficult to achieve efficient ion transmission and osmosis energy conversion.

Method used

Adopt MOF/cellulose composite nanomoid channel membrane, to grow MOF particles by loading growth on cellulose nano -fiber to form a composite film, using the high pore rate of MOF materials and the high negative charging density of cellulose High -efficiency ion transmission.

Benefits of technology

Achieved high ions and ultra-fast ions transmission, and improved the penetration energy conversion performance. The specific manifestation is that under the condition of simulation of seawater/river water at room temperature, the actual power density of the UIO-66-COOH/cellulose composite film can reach 0.9W The actual power density of MN-BTC/cellulose composite membrane can reach 1.9W M-2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115182163B_ABST
    Figure CN115182163B_ABST
Patent Text Reader

Abstract

The present invention discloses a MOF / cellulose composite nanofluid channel membrane and a preparation method and application thereof, wherein MOF particles are loaded and grown on cellulose nanofibers, and then a MOF / cellulose composite membrane is formed, wherein the MOF / cellulose composite membrane has abundant nanochannels inside. The raw materials involved in the MOF / cellulose composite nanofluid channel membrane of the present invention are widely available and are green and environmentally friendly, and the preparation method is simple and universal. The prepared composite membrane material has high charge density and layered nanochannels, high ion flux, and exhibits ultrafast ion transmission, and exhibits high osmotic energy conversion performance in energy conversion applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nanofluid devices, and specifically relates to a MOF / cellulose composite nanofluid channel membrane and a preparation method and application thereof. Background Art

[0002] Obtaining energy from renewable natural resources at low cost is a major challenge in addressing energy dependence. Osmotic energy, also often referred to as salinity gradient energy or "blue energy", is a clean and sustainable energy source that exists in the salinity difference between low-concentration and high-concentration liquids. The difference in salinity between seawater and river water determines the rich osmotic energy between river water and seawater. It is reported that the power of mixing river water and seawater is as high as 0.8kWh / m3. The theoretical amount of osmotic energy in the world can reach more than 1tw, which can meet about 10% of global energy consumption. In recent years, more and more research has been devoted to osmotic energy conversion, and reverse electrodialysis based on nanofluid membranes is a key technology for converting osmotic energy into electrical energy. However, nanofluid membranes synthesized by traditional methods still have problems such as complex preparation methods, high raw material costs, low charge density, poor water stability, high ion transport energy barriers and low current output. Therefore, it is necessary to find materials with better stability, mechanical flexibility, high efficiency, sustainability and low economic cost to construct structure-controllable nanofluids for efficient ion transport.

[0003] Cellulose nanofiber (CNF) is the most widely distributed and abundant biomass material in nature. It is renewable, biodegradable and biocompatible. It also has excellent flexibility and its high aspect ratio gives it excellent mechanical strength. CNF prepared by TEMPO oxidation contains abundant hydroxyl and carboxyl groups and high negative charge density. At the same time, the space formed between the fibers can be used as nanochannels for ion transport. The combination of high surface charge and spatial restriction helps to achieve efficient ion transport. In addition, the hydroxyl groups on the cellulose molecular chain can also form a large number of hydrogen bonds with other nanomaterials, promoting its application potential as a reinforcing material. MOF materials are porous materials with specific crystal structures formed by the interconnection of inorganic metal ions (or metal clusters) and organic ligands. They are very attractive in the field of selective separation due to their high porosity, multifunctional pore structure and adjustable pore size. At the same time, the pore size of MOF materials is usually less than 1nm. The size of such micropores is comparable to the hydration diameter of metal ions. The high surface charge of MOF materials can also be achieved through the reasonable selection and regulation of ligands. Therefore, it has excellent ion conductivity, ion selectivity and high ion flux, and is a promising nanofluid device material. However, since most MOF materials exist in the form of particles or powders, their rigidity and fragility limit their practical applications. Summary of the invention

[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a MOF / cellulose composite membrane with high ion flux and ultrafast ion transport and a preparation method thereof in view of the deficiencies in the prior art.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A MOF / cellulose composite nanofluid channel membrane is provided. MOF particles are loaded and grown on cellulose nanofibers, and then a MOF / cellulose composite membrane is formed. The MOF / cellulose composite membrane has abundant nanochannels inside.

[0007] Preferably, the MOF particles are Mn-BTC or UiO-66-COOH.

[0008] Furthermore, the present invention also provides a method for preparing the above MOF / cellulose composite nanofluid channel membrane, which specifically comprises the following steps:

[0009] (1) preparing a cellulose nanofiber solution;

[0010] (2) in the cellulose nanofiber solution of step (1), using an in-situ growth method to uniformly attach MOF particles to the cellulose nanofibers to obtain a MOF / cellulose precursor solution;

[0011] (3) The MOF / cellulose precursor solution in step (2) is vacuum filtered, and the resulting sediment is dried and then peeled off from the substrate.

[0012] In step (1), the cellulose nanofiber solution is obtained by TEMPO oxidation method:

[0013] The dried pulp is dispersed in deionized water to form a uniform pulp suspension; the TEMPO reagent and NaBr are completely dispersed in deionized water, and then added to the pulp suspension, the pH is adjusted to 9-11, and the reaction is stirred at room temperature for 2-4 hours; after the reaction is completed, the reacted pulp is washed with deionized water to neutrality; finally, a transparent gel-like cellulose nanofiber solution is obtained by high-pressure homogenization and mechanical shearing.

[0014] Step (2) specifically includes the following steps:

[0015] S1: Dissolve the metal center in deionized water or ethanol and obtain a uniform metal solution by ultrasonication;

[0016] S2: dissolving the organic ligand in deionized water or ethanol and ultrasonicating to obtain a uniform organic ligand solution;

[0017] S3: dispersing the gel-like cellulose nanofibers in water and subjecting them to mechanical stirring to obtain a uniformly dispersed cellulose nanofiber solution;

[0018] S4: the metal solution obtained in step S1 and the cellulose nanofiber solution obtained in step S3 are mixed and stirred sufficiently to make the metal ions evenly attached to the cellulose nanofibers, thereby obtaining a uniform metal organic framework material / cellulose nanofiber mixed solution;

[0019] S5: slowly drop the organic ligand solution obtained in step S2 into the metal organic framework material / cellulose nanofiber mixed solution obtained in step S3, and mechanically stir and mix them evenly to obtain a MOF / cellulose precursor solution.

[0020] Alternatively, in step S5, the metal organic framework material is Mn-BTC, and the Mn-BTC / cellulose nanofiber mixed solution is mechanically stirred at room temperature and pressure for more than 24 hours to obtain a MOF / cellulose precursor solution.

[0021] Alternatively, in step S5, the metal organic framework material is UiO-66-COOH, and the UiO-66-COOH / cellulose nanofiber mixed solution is stirred and reacted at 100-110° C. for more than 48 hours to obtain a MOF / cellulose precursor solution.

[0022] Preferably, in step (2), the mass fraction of MOF material in the obtained MOF / cellulose precursor solution is 1-10%.

[0023] Specifically, in step (3), the MOF / cellulose precursor solution is ultrasonically treated to obtain a uniform mixed solution, and the mixed solution is then vacuum filtered through a filtration device equipped with a cellulose ester microporous membrane or an organic filter membrane, and the resulting sediment is dried and peeled off from the substrate; the pore size range of the cellulose ester microporous membrane or the organic filter membrane is 0.2-0.3 μm.

[0024] Furthermore, the present invention also claims to protect the use of the above-mentioned MOF / cellulose composite nanofluid channel membrane in the preparation of nanofluid devices.

[0025] Beneficial effects:

[0026] (1) The raw materials involved in the MOF / cellulose composite nanofluid channel membrane of the present invention are widely available and are green and environmentally friendly. The preparation method is simple and universal. The prepared composite membrane material has high charge density and layered nanochannels, high ion flux, and exhibits ultrafast ion transport, and exhibits high osmotic energy conversion performance in energy conversion applications.

[0027] (2) The actual power density of the MOF / cellulose composite nanofluid channel membrane of the present invention can reach 0.9 W m under simulated seawater / river water conditions at room temperature.-2 The actual power density of the Mn-BTC / cellulose composite membrane can reach 1.9 W m -2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0029] Figure 1 The photos and electron microscope images of the Mn-BTC / cellulose composite membrane prepared in Example 1;

[0030] Figure 2 The photograph and electron microscope image of the UiO-66-COOH / cellulose composite membrane prepared in Example 2;

[0031] Figure 3 The zeta potential of the Mn-BTC / cellulose composite membrane prepared in Example 1 at different Mn-BTC loading amounts;

[0032] Figure 4 The zeta potential of the UiO-66-COOH / cellulose composite membrane prepared in Example 2 at different UiO-66-COOH loading amounts and different pH conditions;

[0033] Figure 5 The IV curve of the Mn-BTC / cellulose composite membrane prepared in Example 1 in potassium chloride electrolytes with different concentrations;

[0034] Figure 6 Graph showing the ionic conductivity of the Mn-BTC / cellulose composite membrane prepared in Example 1 in potassium chloride electrolytes of different concentrations;

[0035] Figure 7 The IV curve of the Mn-BTC / cellulose composite membrane prepared in Example 1 in potassium chloride electrolyte with different concentration gradients;

[0036] Figure 8 The output power density of the Mn-BTC / cellulose composite membrane prepared in Example 1 at different Mn-BTC loadings under simulated seawater / river water conditions;

[0037] Fig. 9 This is a graph of the ionic conductivity of the UiO-66-COOH / cellulose composite membrane prepared in Example 2 in potassium chloride electrolytes of different concentrations;

[0038] Fig.10 The output power density of the UiO-66-COOH / cellulose composite membrane prepared in Example 2 at different UiO-66-COOH loadings under simulated seawater / river water conditions;

[0039] Fig.11 pH responsiveness of the UiO-66-COOH / cellulose composite membrane prepared in Example 2. DETAILED DESCRIPTION

[0040] The present invention can be better understood with reference to the following examples.

[0041] Example 1

[0042] The preparation of Mn-BTC / cellulose composite membrane is carried out in the following specific steps:

[0043] (1) Preparation of cellulose nanofibers: First, weigh 3 g of oven-dried pulp and disperse it in 300 mL of deionized water by mechanical stirring to form a uniform pulp suspension; second, completely disperse 0.045 g of TEMPO reagent and 0.3 g of NaBr in deionized water and then add them to the above suspension; add 0.5 M NaOH aqueous solution to the suspension using a pH meter to adjust the pH of the suspension to 10, stir the suspension at room temperature for 2 hours, then wash the reacted pulp with deionized water until it is neutral, and finally, obtain a transparent gel-like fiber solution by mechanical shearing with high-pressure homogenization. Before use, the prepared cellulose nanofibers were stored at 4°C.

[0044] (2) Preparation of Mn-BTC / cellulose precursor solution: Weigh 50 mg of cellulose nanofibers and disperse them in 40 ml of water to obtain a uniformly dispersed nanocellulose suspension; weigh 1.73 mg of manganese acetate tetrahydrate and 3.52 mg of polyvinyl pyrrolidone and dissolve them in 1 ml of water and 1 ml of ethanol and stir them thoroughly to obtain solution A; weigh 2.96 mg of trimesic acid and dissolve them in 1 ml of water and 1 ml of ethanol and stir them thoroughly to obtain solution B; slowly add solutions A and B to the stirring cellulose nanofiber solution in sequence, mechanically stir for 30 min, and let stand at room temperature for 24 h to obtain the Mn-BTC / cellulose precursor solution.

[0045] (3) Preparation of Mn-BTC / cellulose composite membrane: The Mn-BTC / cellulose precursor solution was ultrasonically treated for 20 min, and then the uniform Mn-BTC / cellulose precursor solution was vacuum filtered through a filtration device equipped with an organic filter membrane with a pore size of 0.22 μm, and the sediment was washed three times with deionized water and ethanol to remove foreign ions. Finally, the sediment was dried in air for 4 days, and the composite membrane was peeled off from the substrate. The photographs and electron micrographs of the prepared Mn-BTC / cellulose composite membrane (Mn-BTC loading was 1%) are shown in Figure 2. Figure 1 shown.

[0046] According to the same method as above, Mn-BTC / cellulose composite membranes with Mn-BTC loading amounts of 0.5wt%, 1wt%, 2wt% and 3wt% were prepared.

[0047] Example 2

[0048] Preparation of UiO-66-COOH / cellulose composite membrane, the specific implementation steps are as follows:

[0049] (1) Preparation of cellulose nanofibers: First, weigh 3 g of oven-dried pulp and disperse it in 300 mL of deionized water by mechanical stirring to form a uniform pulp suspension; second, completely disperse 0.045 g of TEMPO reagent and 0.3 g of NaBr in deionized water and then add them to the above suspension; add 0.5 M NaOH aqueous solution to the suspension using a pH meter to adjust the pH of the suspension to 10, stir the suspension at room temperature for 2 hours, then wash the reacted pulp with deionized water until it is neutral, and finally, obtain a transparent gel-like fiber solution by mechanical shearing with high-pressure homogenization. Before use, the prepared cellulose nanofibers were stored at 4°C.

[0050] (2) Preparation of UiO-66-COOH / cellulose precursor solution: Weigh a certain amount of gel-like cellulose nanofibers, zirconium chloride and 1,2,4-benzenetricarboxylic acid powder to keep the total mass at 50 mg, of which 6 wt% UiO-66-COOH and 94 wt% cellulose nanofibers; put the gel-like cellulose nanofibers into a beaker and add deionized water to a volume of 30 mL, and perform mechanical stirring for 60 minutes to obtain a uniformly dispersed suspension; add zirconium chloride powder into 10 mL deionized water and perform ultrasonic treatment for 20 minutes, and then slowly add it dropwise to The mixture was then mechanically stirred for 24 hours to allow the zirconium ions to evenly adhere to the cellulose nanofibers. 1,2,4-benzenetricarboxylic acid powder was added to 10 mL of deionized water for 20 minutes of ultrasonic treatment, and then slowly added dropwise to the zirconium chloride / cellulose nanofiber mixture for 4 hours of mechanical stirring. The uniform mixture was then transferred to a 100 mL polytetrafluoroethylene-lined high-pressure reactor and placed in an oven at 105°C for continuous reaction for 48 hours. The resulting mixture was the UiO-66-COOH / cellulose precursor solution.

[0051] (3) Preparation of UiO-66-COOH / cellulose composite membrane: The UiO-66-COOH / cellulose precursor solution was ultrasonically treated for 30 minutes, and then the uniform UiO-66-COOH / cellulose precursor solution was vacuum filtered through a filtration device equipped with a cellulose ester microporous membrane, and the sediment was washed alternately with deionized water and methanol for 6 times to remove foreign ions. Finally, the sediment was dried in air for 3 days, and the composite membrane was peeled off from the substrate. The photograph and electron micrograph of the prepared UiO-66-COOH / cellulose composite membrane (UiO-66-COOH loading is 6wt%) are shown in the figure below. Figure 2 shown.

[0052] According to the same method as above, Mn-BTC / cellulose composite membranes with UiO-66-COOH loadings of 3wt%, 6wt%, 8.3wt% and 13.1wt% were prepared.

[0053] Example 3

[0054] The zeta potential test of the Mn-BTC / cellulose composite membrane prepared in Example 1 was carried out as follows:

[0055] (1) Testing the moisture content of Mn-BTC / cellulose composite membrane: Take 1 mL of Mn-BTC / cellulose precursor solution and add it into a weighing bottle of known absolute dry weight. Place it in a 105°C oven for 4 h. Then take out the weighing bottle and place it in a vacuum desiccator for 2 h to cool it down and weigh it. The moisture content of the Mn-BTC / cellulose composite membrane was calculated.

[0056] (2) Deionized water was added to the Mn-BTC / cellulose precursor solution to dilute the solution to a concentration of 1 mg / mL, and the dilution was stirred overnight with a magnetic stirrer to mix well.

[0057] (3) The 1 mg / mL Mn-BTC / cellulose mixture was transferred to a zeta potential cell and the zeta potential was measured using a nano-laser particle size analyzer. Figure 3 It can be seen that as the loading amount of Mn-BTC increases, the zeta potential of the composite membrane decreases.

[0058] Example 4

[0059] The zeta potential test of the UiO-66-COOH / cellulose composite membrane prepared in Example 2 was carried out as follows:

[0060] (1) Testing the moisture content of UiO-66-COOH / cellulose composite membrane: First, the composite membrane was ground into powder, deionized water was added and mixed thoroughly by mechanical stirring and ultrasound, and then 1 mL of the UiO-66-COOH / cellulose mixed solution was added to a weighing bottle of known absolute dry weight, and placed in a 105°C oven for 4 h. Then, the weighing bottle was taken out and placed in a vacuum desiccator for cooling for 2 h and then weighed to calculate the moisture content of the UiO-66-COOH / cellulose composite membrane.

[0061] (2) Deionized water was added to the UiO-66-COOH / cellulose mixture to dilute the solution to a concentration of 1 mg / mL, and the dilution was stirred overnight with a magnetic stirrer to mix evenly.

[0062] (3) The UiO-66-COOH / cellulose mixed solution was adjusted to pH = 7, pH = 9, and pH = 11 using a standard NaOH solution and a 1 mol / L HCl solution through a pH meter.

[0063] (3) The 1 mg / mL UiO-66-COOH / cellulose mixture was transferred to a zeta potential cell and the zeta potential was measured using a nano-laser particle size analyzer. Figure 4 As shown in Figure 3, with the increase of pH, the zeta potential of the composite membrane gradually increased.

[0064] Example 5

[0065] The ion transport performance of the Mn-BTC / cellulose composite membrane prepared in Example 1 was tested, specifically:

[0066] (1) The composite membrane was cut into rectangular blocks and then coated in a homemade two-chamber electrochemical cell. To avoid leakage, a top sealing layer composed of a transparent PDMS elastomer was attached to the composite membrane. Then, two electrolyte reservoirs were carved out in the PDMS elastomer to expose both ends of the composite membrane.

[0067] (2) The IV curve of the composite membrane was measured using a DH7000 electrochemical workstation in potassium chloride electrolyte with different concentrations, with the scanning voltage ranging from -1 V to +1 V. The results are shown in Figure 2. Figure 5 shown.

[0068] (3) Using DH7000 electrochemical workstation, the -6 , 10 -5 , 10 -4 , 10 -3 , 10 -2 , 10 -1 The ionic conductivity of the composite membrane was measured in 1M potassium chloride electrolyte, with the scanning voltage ranging from -1V to +1V. The results are as follows: Figure 6 As shown, CNF in the figure is cellulose nanofiber.

[0069] Example 6

[0070] The osmotic energy conversion performance test of the Mn-BTC / cellulose composite membrane prepared in Example 1 was carried out, specifically:

[0071] (1) The composite membrane was cut into rectangular blocks and then coated in a homemade two-chamber electrochemical cell. To avoid leakage, a top sealing layer composed of a transparent PDMS elastomer was attached to the composite membrane. Then, two electrolyte reservoirs were carved out in the PDMS elastomer to expose both ends of the composite membrane.

[0072] (2) Using Keithley to measure IV curves under different concentration gradients in a potassium chloride electrolyte with a concentration gradient, the short-circuit current I SC and open circuit voltage V OC The potassium chloride electrolyte concentration on the low concentration side is fixed at 10 -4 M, change the potassium chloride electrolyte concentration on the high concentration side, scan the voltage from -1V to +1V, the results are as follows Figure 7 As shown in Figure C L Indicates the potassium chloride electrolyte concentration on the low concentration side, fixed at 10 -4 M, CH represent the potassium chloride electrolyte concentration on the high concentration side, which are 10 -3 , 5×10 -2 , 10 -1 M.

[0073] (3) The transmembrane potential was measured using a standard Ag / AgCl electrode.

[0074] (4) Connect the circuit by connecting an external load resistance box, adjust the external resistance from 1000Ω to 10MΩ, and use an electrochemical workstation to record the change in ion current as the load resistance increases. 2 R / S obtained the output power density value, which reflects the osmotic energy conversion performance of the composite membrane nanochannel. The results are as follows Figure 8 As shown, the maximum output power density is obtained when the Mn-BTC loading is 1 wt%.

[0075] Example 7

[0076] The ion transport performance of the UiO-66-COOH / cellulose composite membrane prepared in Example 2 was tested, specifically:

[0077] (1) The composite membrane was cut into rectangular blocks and then coated in a homemade two-chamber electrochemical cell. To avoid leakage, a top sealing layer composed of a transparent PDMS elastomer was attached to the composite membrane. Then, two electrolyte reservoirs were carved out in the PDMS elastomer to expose both ends of the composite membrane.

[0078] (2) The ionic conductivity of the composite membrane was measured using a DH7000 electrochemical workstation in a potassium chloride electrolyte with a specific concentration, with the voltage scanned from -1 V to +1 V. The results are as follows: Fig. 9 shown.

[0079] (3) The transmembrane potential was measured using a standard Ag / AgCl electrode.

[0080] Example 8

[0081] The osmotic energy conversion performance test of the UiO-66-COOH / cellulose composite membrane prepared in Example 2 was carried out, specifically:

[0082] (1) The composite membrane was cut into rectangular blocks and then coated in a homemade two-chamber electrochemical cell. To avoid leakage, a top sealing layer composed of a transparent PDMS elastomer was attached to the composite membrane. Then, two electrolyte reservoirs were carved out in the PDMS elastomer to expose both ends of the composite membrane.

[0083] (2) Use Keithley to measure IV curves under different concentration gradients in a potassium chloride electrolyte with a concentration gradient and record the short-circuit current I SC The potassium chloride electrolyte concentration on the low concentration side is fixed at 10 -4 M, change the potassium chloride electrolyte concentration on the high concentration side, and scan the voltage from -1V to +1V.

[0084] (3) The circuit was connected through an external load resistor box and the transmembrane potential was measured using a standard Ag / AgCl electrode.

[0085] (4) By adjusting the external resistance from 1000Ω to 10MΩ, the Keithley system was used to record the change in ion current under different conditions as the load resistance increased. The formula P = I 2 R / S obtained the output power density value, which reflects the osmotic energy conversion performance of the composite membrane nanochannel. The results are as follows Fig.10 shown.

[0086] (5) The pH of the electrolyte solution was adjusted to pH = 7, pH = 9, and pH = 11, and the output power density of the composite membrane under different pH conditions was recorded using Keithley. Fig.11 As shown in Figure 3, as the pH increases, the output power density of the composite membrane increases.

[0087] The present invention provides a MOF / cellulose composite nanofluid channel membrane and its preparation method and application ideas and methods. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. Application of a MOF / cellulose composite nanofluid channel membrane in the preparation of nanofluid devices, characterized in that: Loading and growing MOF particles on cellulose nanofibers, and then forming a MOF / cellulose composite membrane, wherein the MOF / cellulose composite membrane has abundant nanochannels inside; The MOF particles are Mn-BTC or UiO-66-COOH; The MOF / cellulose composite nanofluid channel membrane is prepared by the following steps: (1) preparing a cellulose nanofiber solution; (2) in the cellulose nanofiber solution of step (1), using an in-situ growth method to uniformly attach MOF particles to the cellulose nanofibers to obtain a MOF / cellulose precursor solution; (3) vacuum filtering the MOF / cellulose precursor solution in step (2), and drying the resulting sediment, and then peeling it off from the substrate; Step (2) specifically includes the following steps: S1: Dissolve the metal center in deionized water or ethanol and obtain a uniform metal solution by ultrasonication; S2: dissolving the organic ligand in deionized water or ethanol and ultrasonicating to obtain a uniform organic ligand solution; S3: dispersing the gel-like cellulose nanofibers in water and subjecting them to mechanical stirring to obtain a uniformly dispersed cellulose nanofiber solution; S4: the metal solution obtained in step S1 and the cellulose nanofiber solution obtained in step S3 are mixed and stirred sufficiently to make the metal ions evenly attached to the cellulose nanofibers, thereby obtaining a uniform metal organic framework material / cellulose nanofiber mixed solution; S5: slowly dropwise adding the organic ligand solution obtained in step S2 to the metal organic framework material / cellulose nanofiber mixed solution obtained in step S3, and mechanically stirring and mixing to obtain a MOF / cellulose precursor solution; In step S5, when the metal organic framework material is Mn-BTC, the Mn-BTC / cellulose nanofiber mixed solution is mechanically stirred at room temperature and pressure for more than 24 hours to obtain a MOF / cellulose precursor solution; When the metal organic framework material is UiO-66-COOH, the UiO-66-COOH / cellulose nanofiber mixed solution is stirred and reacted at 100-110° C. for more than 48 h to obtain a MOF / cellulose precursor solution.

2. The use of the MOF / cellulose composite nanofluid channel membrane according to claim 1 in preparing nanofluid devices, characterized in that: In step (1), the cellulose nanofiber solution is obtained by TEMPO oxidation method: The dry pulp is dispersed in deionized water to form a uniform pulp suspension; the TEMPO reagent and NaBr are completely dispersed in deionized water, then added to the pulp suspension, the pH is adjusted to 9-11, and the reaction is stirred at room temperature for 2-4 hours; after the reaction is completed, the reacted pulp is washed with deionized water to neutrality; finally, a transparent gel-like cellulose nanofiber solution is obtained by high-pressure homogenization and mechanical shearing.

3. The use of the MOF / cellulose composite nanofluid channel membrane according to claim 1 in preparing nanofluid devices, characterized in that: In step (2), the mass fraction of MOF material in the obtained MOF / cellulose precursor solution is 1-10%.

4. The use of the MOF / cellulose composite nanofluid channel membrane according to claim 1 in preparing nanofluid devices, characterized in that: In step (3), the MOF / cellulose precursor solution is ultrasonically treated to obtain a uniform mixed solution, and the mixed solution is then vacuum filtered through a filtration device equipped with a cellulose ester microporous membrane or an organic filter membrane. The resulting sediment is dried and peeled off from the substrate; the pore size range of the cellulose ester microporous membrane or the organic filter membrane is 0.2-0.3 μm.

Citation Information

Patent Citations

  • KR20210017746A